Nano Liposomal Curcumin as an Adjuvant: Enhancing Cisplatin Anticancer Effects in HeLa Cells - Subandi, Subandi; Balindra, Fredlina Rossa; Gizta, Aura Bella; Khotimah, Husnul; Handono, Kusworini (Sciences of Pharmacy, 2025)
Cervical cancer, mainly driven by oncogenic HPV infections, remains a global health burden. Cisplatin is standard chemotherapy for advanced cases but is limited by toxicity. Nano liposomal curcumin, with improved bioavailability, may enhance cisplatin’s efficacy. This study investigated the combination’s effect on HeLa cells by analyzing Cyclin E1 and Bcl-2 expression. Nano liposomal curcumin was synthesized using thin-film hydration, yielding stable 32 nm nanoparticles. HeLa cells were divided into control and treatment groups, and varying doses of nano liposomal curcumin with cisplatin were received. Flow cytometry revealed significant reductions in Cyclin E1 (from 18.62 ± 1.45 to 5.79 ± 0.47) and Bcl-2 (from 32.56 ± 0.82 to 28.19 ± 0.30) at the highest dose (p < 0.05). Cell viability decreased to 9% with cisplatin alone and 1% with the combination. These results indicate that nano liposomal curcumin enhances cisplatin’s antiproliferative and pro-apoptotic effects, supporting its potential as an adjuvant to lower cisplatin doses while maintaining efficacy. Further research involving additional molecular markers, in vivo models, and clinical trials is needed to optimize dosing, confirm safety, and evaluate therapeutic potential.